An immune gene expression signature distinguishes central nervous system metastases from primary tumours in non–small-cell lung cancer. (June 2020) - Tsakonas, Georgios; Lewensohn, Rolf; Botling, Johan; Ortiz-Villalon, Cristian; Micke, Patrick; Friesland, Signe; Nord, Helena; Lindskog, Magnus; Sandelin, Martin; Hydbring, Per; Ekman, Simon
Abstract: Background: Dissemination of non–small-cell lung cancer (NSCLC) in the central nervous system is a frequent and challenging clinical problem. Systemic or local therapies rarely prolong survival and have modest activity regarding local control. Alterations in gene expression in brain metastasis versus primary tumour may increase aggressiveness and impair therapeutic efforts. Methods: We identified 25 patients with surgically removed NSCLC brain metastases in two different patient cohorts. For 13 of these patients, primary tumour samples were available. Gene expression analysis using the nCounter® PanCancer Immune Profiling gene expression panel (nanoString technologies Inc.) was performed in brain metastases and primary tumour samples. Identification of differentially expressed genes was conducted on normalized data using the nSolver analysis software. Results: We compared gene expression patterns in brain metastases with primary tumours. Brain metastasis samples displayed a distinct clustering pattern compared to primary tumour samples with a statistically significant downregulation of genes related to immune response and immune cell activation. Results from KEGG term analysis on differentially expressed genes revealed a concomitant enrichment of multiple KEGG terms associated with the immune system. We identified a 12-gene immune signature that clearly separated brain metastases from primary tumours. Conclusions: We identified a unique gene downregulation pattern in brain metastases compared with primary tumours. This finding may explain the lower intracranial efficacy of systemic therapy, especially immunotherapy, in brain metastasis of patients with NSCLC. Highlights: Gene expression matched analysis was performed in primary vs brain metastatic non–small-cell lung cancer (NSCLC). We identified a unique immune gene downregulation pattern in brain metastatic NSCLC. A diagnostic 12-gene signature for brain metastatic NSCLC was identified.